(untitled) (Eurasian Journal of Ecology, 2019)
The production of silica from rice husk (RH) is a promising direction of modern research. RH is considered waste and must be disposed of by incineration. This waste can cause a fire, and the amount of smoke that is emitted leads to environmental pollution. The negative impact of RH waste is exacerbated by the fact that RH dust is a source of respiratory tract infection in people living nearby. Analysis of the technology for producing silicon dioxide from RH showed that, depending on the state of combustion, the type of furnace, the variety of rice, climate and other components, RH ash may contain silicon oxide 10-20% and other organic compounds. In many countries, including Kazakhstan, the development of technology for the production of silicon oxide from RS is becoming increasingly popular due to the increased consumption of amorphous silicon oxide, widely used in various industries. In this regard, this paper discusses the issues of obtaining high-purity silicon oxide and the determination of its characteristics. The methods used were: X-ray diffraction (XRD), infrared spectroscopy (IR), FTIR spectra of silicon extracted from RH, as well as thermograms and SEM images. As a result of the research, silicon dioxide SiO 2 was obtained with a purity of about 99.5%. Thus, obtain silicon dioxide indicates the prospects and effectiveness of using RH as a cheap raw material for the production of materials based on silicon. Key words: rice husk, nanoparticles, silica, hydrochloric acid, amorphous silicon.